2021
DOI: 10.3233/jad-201187
|View full text |Cite|
|
Sign up to set email alerts
|

Cognition at Each Stage of Lewy Body Disease with Co-occurring Alzheimer’s Disease Pathology1

Abstract: Background: Alzheimer’s disease neuropathologic change (ADNC) may contribute to dementia in patients with Lewy body disease (LBD) pathology. Objective: To examine how co-occurring ADNC impacts domain specific cognitive impairments at each pathologic stage (brainstem, limbic, cerebral cortical) of LBD. Methods: 2,433 participants with antemortem longitudinal neuropsychological assessment and postmortem neuropathological assessment from the National Alzheimer’s Coordinating Center’s Uniform Data Set were charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 57 publications
2
19
0
Order By: Relevance
“…S1) were comparable between pure-AD and AD-LB. Previous studies have similarly suggested that co-morbid LB pathology exacerbates AD-typical cognitive deficits but does not necessarily produce a mixed clinical phenotype (7,13,14), while others did observe more DLB symptomatology in AD-LB cases (8)(9)(10)(11)(12)39). These differences may be explained by different clinico-pathologic definitions of the AD-LB groups, as some autopsy studies define the different pathology groups based solely on neuropathologic criteria (8,39), while others also restrict their samples to a particular clinical phenotype as in our study (6,13,20,23).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…S1) were comparable between pure-AD and AD-LB. Previous studies have similarly suggested that co-morbid LB pathology exacerbates AD-typical cognitive deficits but does not necessarily produce a mixed clinical phenotype (7,13,14), while others did observe more DLB symptomatology in AD-LB cases (8)(9)(10)(11)(12)39). These differences may be explained by different clinico-pathologic definitions of the AD-LB groups, as some autopsy studies define the different pathology groups based solely on neuropathologic criteria (8,39), while others also restrict their samples to a particular clinical phenotype as in our study (6,13,20,23).…”
Section: Discussionmentioning
confidence: 98%
“…Although AD and DLB have unique neuropathological profiles, up to 60% of clinical AD and DLB patients present with neuropathological findings of both diseases (5,6). Concomitant LB pathology in clinical AD has been associated with faster cognitive decline (7)(8)(9), younger age at death (8), and more DLB-like clinical features (9)(10)(11)(12), although this could not be confirmed by others (7,13,14). In the era of disease-modifying therapies, these patients may benefit less from amyloid-lowering therapies (15), whereas they may potentially show a better response to cholinesterase inhibitors (16).…”
Section: Introductionmentioning
confidence: 93%
“…Confrontation naming can be assessed using physical objects or line drawings of objects of varying frequency as visual stimuli, such as in the Boston Naming Test. Episodic memory loss and deficits in confrontation naming are linked to temporal lobe functioning, and in PDD/DLB is associated with underlying mixed AD tau pathology 61,62 . Thus, the presence of significant levels of AD neuropathology in Lewy body disorders may influence the clinical expression of dementia.…”
Section: Dementia With Lewy Bodiesmentioning
confidence: 99%
“…Episodic memory loss and deficits in confrontation naming are linked to temporal lobe functioning, and in PDD/DLB is associated with underlying mixed AD tau pathology. 61,62 Thus, the presence of significant levels of AD neuropathology in Lewy body disorders may influence the clinical expression of dementia.…”
Section: Dementia With Lewy Bodiesmentioning
confidence: 99%
“…Mixed dementia in which neuropathologies overlap is common, and different diseases may also have related characteristics. For instance, AD pathology is present in 10–59% of patients with LBD, with synergizing effects that may act on distinct cognitive domains [ 4 ]. Another example is found in PD and LBD, distinct disorders that both involve the aggregation of lewy bodies in the brain made up of α-synuclein [ 5 ].…”
Section: Introductionmentioning
confidence: 99%